Analytical Tools To Assist Climate-Smart Agriculture Policy Making - Rosegrant, Mark W. (International Food Policy Research Institute, 2015)
Presented by Mark W. Rosegrant, IFPRI, at GFIA 2015, Abu Dhabi, UAE. Mark highlighted that CSA forces us to shifts the emphasis from policies that aim at a single targets to policies that have multiple objectives. He went on to underline that CSA changes the planning time horizon - policies and analyses necessarily span long time periods of 20-30 years. And that therefore CSA requires the use of integrated modeling frameworks that work at multiple geographical scales. And that given its complexity, importantly, CSA requires an even closer collaboration between policy makers and research community.